2000
DOI: 10.1046/j.1365-2842.2000.00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alteration of occlusal relationship on activity of jaw closing muscles and mandibular movement during submaximal clenching

Abstract: The aim of this study was to investigate the relationships between occlusal contacts, responses of muscles, and jaw movements during simulated clenching. Seven healthy human males who possessed complete natural dental arches with normal occlusion, ranging from 24 to 29 years of age, volunteered for this study. Acrylic occlusal stops were fabricated for the lower jaw to simulate various occlusal conditions. Vertical movements of the lower jaw were measured by four sets of linear variable differential transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…However, there were no significant changes in 2, 4 and 6 weeks after the insertion of either splint (Baba et al, 2000).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, there were no significant changes in 2, 4 and 6 weeks after the insertion of either splint (Baba et al, 2000).…”
Section: Discussionmentioning
confidence: 70%
“…In another patient it could be observed an inverse situation: significant differences on EMG signs on the right masseter and no significant differences on EMG signs on the left masseter. This situation of different results found in masseter muscles of the same individual can be explained by (Baba et al, 2000), which showed that inadequate force distribution of the masticatory muscles and temporomandibular joints, can lead to occlusal asymmetry.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Christensen and Rassouli have reported motor facilitation on the masseter muscle on the side of a rigid unilateral interference and motor inhibition on the opposite side during forceful clenching (Christensen and Rassouli, 1995). According to Baba, an increase in the activity of anterior temporalis ipsilateral muscle will also occur, when an interference is placed (Baba et al , 2000). Using EMG, Belser and Hannam (Belser and Hannam, 1985) reported that lateral clenching efforts on the natural canine caused unilateral activity in the anterior and posterior temporal muscles with clear dominance on the working-side; the introduction of an experimental balancing interference changed these unilateral activity patterns to bilateral.…”
Section: Introductionmentioning
confidence: 99%
“…Ursachen für Bruxismus können sowohl zentral als auch peripher liegen [33]. Es gibt bislang allerdings nur widersprüchliche Angaben darüber, ob und wie die Zahnstellung (oder deren Veränderung im Zuge kieferorthopädischer Behandlungen) Einfluss auf Bruxismusaktivitäten nimmt [1,39,40].…”
Section: Design Overviewunclassified
“…Bruxism can have central and peripheral causes [33]. However, there has been controversy as to if and how tooth position (or its change due to orthodontic treatment) affects bruxing behavior [1,39,40].…”
Section: Introductionmentioning
confidence: 99%